2017
DOI: 10.1111/1759-7714.12474
|View full text |Cite
|
Sign up to set email alerts
|

Clinico‐radiological features and next generation sequencing of pulmonary epithelioid hemangioendothelioma: A case report and review of literature

Abstract: Epithelioid hemangioendothelioma is a very rare, vascular, low‐grade malignant tumor found in the lungs, liver, bone, and other soft tissues. Most patients with pulmonary epithelioid hemangioendothelioma (PEH) are asymptomatic but usually present with multiple bilateral nodular lesions in the lungs. Currently, surgical lung biopsy, histology, and immunohistochemical methods are essential for diagnosis. However, there is no standard therapy for the treatment for PEH.Our paper describes the clinico‐radiologic fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Therefore, it is necessary to detect corresponding mutated genes and then select the most effective therapeutic schedule. Compared with traditional detection methods, NGS has the advantage of offering a single-time high-throughput detection of the status and changes of multiple genes in vivo, enriching the rigid requirements for clinical diagnosis, treatment, and continuous monitoring of HCC prognosis [ 35 , 36 ]. Biopsy is the gold standard diagnostic method for solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to detect corresponding mutated genes and then select the most effective therapeutic schedule. Compared with traditional detection methods, NGS has the advantage of offering a single-time high-throughput detection of the status and changes of multiple genes in vivo, enriching the rigid requirements for clinical diagnosis, treatment, and continuous monitoring of HCC prognosis [ 35 , 36 ]. Biopsy is the gold standard diagnostic method for solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…6 Another study has confirmed that the occurrence of this disease is related to chronic bartonella infection, which is related to the invasion and induction of Bartonella into red blood cells intradermal infection and at least three Bartonella species induce vascular endothelial factor mediated proliferation, cytoskeleton rearrangement, and inhibit endothelial cell apoptosis by upregulating mitosis and proinflammatory genes. 7 EHE tends to occur in middle-aged women, and the incidence rate is 2-4 times that of men. More than 40% of patients are younger than 30 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear expression of CAMTA and TFE can be detected as a result of WWTR1–CAMTA1 and YAP1–TFE3 fusions ( 5 , 6 ). Disease-related genetic changes that can be detected using next-generation sequencing may be useful in predicting treatment response ( 19 ). Although next-generation sequencing was performed in our patient, no significant mutations were identified.…”
Section: Discussionmentioning
confidence: 99%